ANALISIS DESAIN KEMASAN, HARGA, KUALITAS PRODUK DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS MEDAN CRISPY 22 M2C DESA SAMPALI PRECUT SEI TUAN - hanum, hamidah (MTU PRESS, 2022)
This research is motivated by the existence of competition in the management of home-made fried onions in Medan. Competition for homemade fried onions that has become increasingly stringent recently has had an effect on the business of Medan Crispy Fried Onions 22. The increasing number of consumer choices for fried onions managed by the people in the city of Medan, makes consumers more free to choose which fried onions suit their tastes and can afford them. make ends meet. This has made fried onion business actors in Medan vying to deliver the best quality products. Therefore, this research tries to examine the development of the culinary industry for fried onion products in Medan Crispy 22 so that the business can survive until now and continue to experience an increase in sales. This study aims to determine the effect of packaging design, price and product quality on purchasing decisions of Medan Crispy 22 M2C. This type of research uses quantitative research methods with primary and secondary data sources. The number of samples in this study is 100 respondents who are influenced by using the Wibisono formula and purposive sampling technique, namely the technique of determining the sample according to certain considerations. This study uses SPSS 26.0 as a data cooking tool. What will happen this research proves that partially packaging design has no significant effect on purchasing decisions, while price and product quality partially have a positive and significant effect on purchasing decisions. while simultaneously showing that packaging design, price and product quality together have a positive and significant effect on purchasing decisions.